MicroRNA‐200c overexpression in cancer‐associated fibroblasts decreases interleukin‐2 secretion. Issue 2 (10th June 2022) - Shariati, Laleh; Vaseghi, Golnaz; Vaziri, Nazanin; Shenavar, Nasim; Zarrabi, Ali; Haghjooy Javanmard, Shaghayegh
Abstract: miR‐200c‐3p is demonstrated to play the role of tumour suppressor in different tumours. However, the miR‐200c‐3p biological function in normal fibroblast (NF) and cancer‐associated fibroblast (CAF) remains unclear. This investigation aims to study the regulatory role of miR‐200c‐3p in the secretion of Interleukin‐2 (IL‐2) in CAF and NF. CAFs and NFs were isolated from tumour and normal tissue specimens respectively. Immunocytochemistry was used to confirm the presence of a fibroblast specific marker, alpha‐actin smooth muscle, in NFs and CAFs. NF and CAF were transfected with scramble and miR‐200c‐3p utilizing the lipofectamine 2000 reagent. The protein levels of IL‐2 were measured in CAFs, NFs, and transfected groups with miR‐200c‐3p and scrambled using an IL‐2 enzyme‐linked immunoassay kit. miR‐200c decreased secretion of IL‐2 in transfected CAF and NF compared to controls. Results elucidated that transfection of MiR‐200c‐3p can decrease the IL‐2 secretion and consequently reduce IL‐induced tumourigenic manner in the CAF. Abstract : MiR‐200c‐3p transfection decreases the Interleukin‐2 (IL‐2) secretion level, resulting in a reduction in IL‐induced tumourigenic manner of cancer‐associated fibroblast.